Discovery of a monophagous true predator, a specialist termite-eating spider (Araneae: Ammoxenidae) - Petráková, Lenka; Líznarová, Eva; Pekár, Stano; Haddad, Charles R; Sentenská, Lenka; Symondson, William O C (Scientific reports, 2015)
True predators are characterised by capturing a number of prey items during their lifetime and by being generalists. Some true predators are facultative specialists, but very few species are stenophagous specialists that catch only a few closely related prey types. A monophagous true predator that would exploit a single prey species has not been discovered yet. Representatives of the spider family Ammoxenidae have been reported to have evolved to only catch termites. Here we tested the hypothesis that Ammoxenus amphalodes is a monophagous termite-eater capturing only Hodotermes mossambicus. We studied the trophic niche of A. amphalodes by means of molecular analysis of the gut contents using Next Generation Sequencing. We investigated their willingness to accept alternative prey and observed their specific predatory behaviour and prey capture efficiency. We found all of the 1.4 million sequences were H. mossambicus. In the laboratory A. amphalodes did not accept any other prey, including other termite species. The spiders attacked the lateral side of the thorax of termites and immobilised them within 1 min. The paralysis efficiency was independent of predator:prey size ratio. The results strongly indicate that A. amphalodes is a monophagous prey specialist, specifically adapted to feed on H. mossambicus.
Keywords: Predatory Behavior; Isoptera; predátorské chování; Spiders; pavouci; Female; mužské pohlaví; ženské pohlaví; Male; zvířata; Animals